Clinical Observation on Basal Ganglia Aphasia after Stroke Treated by Donepezil - Xi CHENG; Jinghui LAI; Zhifeng WANG; Yanling GAO; Xiaofeng CHEN; Ling LIN (康复学报)
Objective:To evaluate the curative effect of donepezil on basal ganglia aphasia after stroke.Methods:A total of 37 patients with basal ganglia aphasia after stroke were randomly assigned to donepezil group (n=19) and control group (n=18). Control group was treated with neural nutrition medicine and speech training for 30 minutes each day. Donepezil group received donepezil at a dose of 5 mg each time additionally, and one time daily. After eight weeks, the MMSE, BDAE and WAB scales were used to evaluate the curative effect before and after the treatment.Results:There was a significant difference in the MMSE, BDAE and WAB scales between the control group and the donepezil group after eight weeks. The curative effect of donepezil group was better than that of control group with mild side reactions and good dependence.Conclusion:Donepezil is safe and effective for the treatment of basal ganglia aphasia after stroke.